The Macmillan science and technology encyclopedia. 1, Ab-Bi - Macmillan (Macmillan Melbourne, 1992)
The Macmillan Science and Technology Encyclopedia is an extensive reference work that covers a broad range of topics in science, technology, engineering, and mathematics (STEM). This encyclopedia provides clear and accessible explanations of scientific principles, technological advancements, and fundamental theories across disciplines such as physics, chemistry, biology, astronomy, computer science, and engineering. Each entry is designed to offer readers a comprehensive yet concise overview, with illustrations and examples to clarify complex concepts. This resource serves as an invaluable tool for students, educators, researchers, and anyone seeking a foundational understanding of modern scientific and technological knowledge.